From Inactivity to Activity: Passive Wheelchair Bike Rides Increase Trapezius Muscle Activity in Non-Ambulant Youth with Disabilities - Lisa Musso-Daury; Celia García-Chico; Susana López-Ortiz; Saúl Peñín-Grandes; Diego del Pozo-González; Rosa Ana Sánchez-García; Laura Marín-Varela; Carmen Matey-Rodríguez; Alejandro Santos-Lozano (Children, 2025)
Background/Objectives: Children at Gross Motor Function Classification System (GMFCS) levels IV and V experience severe motor impairments, yet the effects of passive wheelchair rides on their physiological parameters remain unexplored. This study aimed to examine the acute physiological response to passive bike in non-ambulant children with physical disabilities. Methods: This quasi-experimental study included 24 non-ambulant participants with cognitive impairments (6–21 years old, 50% female). After a 10-min rest, participants underwent a 10-min passive wheelchair bike. Muscle activity, oxygen consumption, and heart rate variability were assessed. Results: Passive bike rides significantly increased muscle activity in the right upper (p = 0.050), left upper (p = 0.008), and left lower trapezius (p = 0.038), with increases of 97–112%. However, no significant changes were observed in oxygen consumption or cardiorespiratory parameters. Conclusions: This study suggests that passive wheelchair bike rides increase trapezius muscle activity in children with severe disabilities at GMFCS levels IV and V, offering potential benefits for this population.